A functionwise analysis of the cruise ports in Turkey: The case of Kusadasi - CENGIZ KAHRAMAN (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This research summarizes the Turkish cruise port system, focusing on the most popular port of Kusadasi, and offers recommendations for improving cruise tourism in the country.Methodology: A qualitative approach was taken, and information was gathered through an extensive literature review and analysis.Findings: The services provided by Turkish ports for cruise ships are inadequate, according to a study of those ports.Implications/novelty: Because cruise tourism is a relatively new industry, this study provides an in-depth examination of the cruise industry in Turkey, identifying key issues and offering concrete recommendations for enhancing the fun and relaxation offered by cruises.